Analysis of Considerations of Mitigating and Aggravating Circumstances in Corruption Crime Cases (Case Study Decision Number 942 K/Pid.Sus/2022) - Ferdinan Januari; Bambang Waluyo (Journal of Law, Politic and Humanities, 2024)
This article is entitled Analysis of Considerations of Mitigating and Aggravating Circumstances in Corruption Crime Cases (Case Study of Decision Number 942 K/Pid.Sus/2022).  This article aims to analyze the application of mitigating and aggravating circumstances in corruption cases as well as finding the influence of these on Decision Number 942K/Pid.Sus/2022.  Using normative juridical methods with a statutory approach, conceptual approach and case approach.  The results of this study show that there are problems regarding the application of mitigating and aggravating circumstances due to differences in the interpretations and views of each judge.  Apart from that, the influence shown by the incompatibility of the application of mitigating and aggravating circumstances can have an impact on not achieving the objectives of the sentence, including retaliation and a deterrent effect on the defendant as found in the corruption case Decision Number 942K/Pid.Sus/2022.